Effects of invasive plants on the health of forest ecosystems on small tropical coral islands. (October 2020) - Cai, Hongyue; Lu, Hongfang; Tian, Yang; Liu, Zhanfeng; Huang, Yao; Jian, Shuguang
Highlights: Plant invasions have desynchronized impacts in above and belowground communities. Invasion of Cassytha filiformis affects soil properties and microbe communities. Eco-exergy can be used as an indicator to detect the effects of plant invasions. Soil phosphorus plays a key role in plant invasions on tropical coral islands. Abstract: Plant invasion is a major factor leading to the degradation of indigenous vegetation on tropical coral islands, where ecosystems are fragile and endemism tends to be high. We analyzed the effects of separate invasions by three plants ( Eupatorium odoratum, Cassytha filiformis, and Wedelia biflora ) on aboveground and belowground communities and on soil properties of forest ecosystems on tropical coral islands. In addition to measuring classical community structure indices (Shannon-Wiener index, evenness, richness, biomass, and density), we measured eco-exergy (Ex) and specific eco-exergy (SpEx). The results showed complicated and desynchronized effects of different plant invasions on the aboveground and belowground biotic communities. The forest plant community was more sensitive to plant invasions than the soil microbial and soil fauna communities. Soil phosphorus explained a large percentage of the variation in the responses to plant invasions. The effects of E. odoratum invasion were less severe than those of C. filiformis or W. biflora invasion. For invasion control and ecosystem restoration, the results indicate that belowground soil biotic restoration should accompany invader removal for managing invasion of C. filiformis and W. biflora, while invader elimination will be sufficient for managing E. odoratum invasion on small coral islands. In assessing responses to plant invasion, Ex showed high sensitivity and monotonicity. Ex could therefore complement classical species-based community structure indices for managing plant invasions and for predicting the ongoing responses to such invasions on fragile, coral island ecosystems.